RECENT RESEARCHES OF THE LATERAL FLEXIBILITY OF RAIL THREAD UNDER COMBINED ACTION OF VERTICAL AND HORIZONTAL FORCES - Danilenko, E. I. (Science and Transport Progress, 2015)
Purpose. Studying the characteristics of spatial flexibility of rail thread is necessary for solving problems in calculation rails durability in full formulation, namely under combined action of vertical and horizontal forces and torque moment on the track. Characteristics of torsional lateral horizontal elasticity and rail thread are the least researched under combined action of vertical and horizontal forces on the track. In the current method of engineering calculation the track durability the impact on track horizontal forces are counted only indirectly through the use of so-called «factors of influence», which are not connected with calculations. That is, the current method cannot let obtain the exact strains and stresses of rails under combined action on the track vertical and horizontal forces. The article purpose is solving the problem of calculation the real lateral modulus of railway track under combined action of vertical and horizontal forces. Methodology. In this paper the complex method of solving the problem was used: with the help of experimental method characteristics of rail horizontal transverse stiffness when exposed only horizontal force were measured; theoretical researches were used for calculation the actual lateral elastic modulus of track Uy(T) (when combined action of vertical and horizontal forces on track takes place). Findings. New data characteristics of lateral flexibility of rail thread were obtained for modern designs of the railway track on concrete and wooden sleepers with rails R65, UIC60, R50, R43 and with fastenings КБ, КПП-5, КПП-1, Д0. Originality. For the first time in domestic researches, experimental and theoretical solution of characteristics of lateral flexibility of rail threads under combined action of vertical and horizontal wheel loads with positioning the functional dependence of variable transverse modulus of the rail elasticity Uy(T) from the ratio of co-operating vertical and horizontal dynamic forces Pdyn / Нdyn . Practical value. The results allow calculating the strength of rail threads considering combined action of vertical and horizontal forces on the track for concrete and wooden sleepers with significantly higher accuracy than with the current method of calculation the track for strength.